Big Nate : attack of the cheez funk breath! - Peirce, Lincoln (Big Nate., 2025)
"Snack-loving sixth-grader Nate Wright always has his hands full--of Cheez Doodles! But those delicious orange curls make his breath stink, and when he tries to quit them cold turkey, poor Nate's a hot mess. And that's not the end of his problems. Out of nowhere, Nate gets dumped by his best buddy Francis. He strikes out at the school dance. And a close encounter at the beach with a spiky-haired look-alike has everyone seeing double. Can our favorite troublemaker turn the funk back into fun?"--